Bio-economic evaluation of cropping systems for saline coastal Bangladesh: I. Biophysical simulation in historical and future environments. (May 2018) - Kabir, Md. Jahangir; Gaydon, Donald S.; Cramb, Rob; Roth, Christian H.
Abstract: Climate change, increased climate variability, extreme weather events, and increasing salinization pose a serious challenge to the sustainability of crop production in coastal Bangladesh. This study assessed yield performance of rice and non-rice crops under farmers' current practices across five climate and three salinity scenarios in the south-western coastal zone. Representative village case studies in Khulna District were used to obtain data on current cropping practices and yields. A validated biophysical crop simulation model (APSIM) was used to simulate performance of crops within 10 cropping systems, representing both existing and potential future cropping patterns. The salinity impact on rice crops was simulated directly using an improved APSIM model, capable of simulating both soil salinity dynamics and the resulting rice crop response. The salinity impact on maize, wheat and sunflower was assessed by developing crop salinity response functions and applying these post-simulation to the crop yields simulated in the absence of salinity. The future performance of some existing crops, namely, watermelon, and pumpkin were extrapolated from data available in the literature and expert knowledge. Climate change is projected to have both positive and negative impacts on crop yields but growing salinity is projected to have substantial negative effects. Allowing for uncertainties inherent in the modelling process, the results indicate that loss of crop production would be negligible under projected 2030 conditions for climate and salinity, even with farmers' current practices. Under 2060 conditions, the adverse impacts on wet-season rice, dry-season rice, and wheat remained negligible, while sunflower experienced notable yield decline. However, the effects of 2060 conditions on early wet season rice and dry-season maize were positive. Climate change in itself does not pose a major risk to crop production and aquaculture in south-west coastal Bangladesh over the next 15–45 years but increasingly salinity will have an unambiguously negative influence. Highlights: Climate change and salinization together threaten cropping in coastal Bangladesh. Simulations showed small yield losses of major crops in 2030 and 2060 conditions. Yields of early-wet-season rice and dry-season maize increased in these conditions. Climate change itself is not a major risk to crop yields over the next 15–45 years. Salinization will have a significant negative impact on all dry-season crops.